<u>Answer:</u>
The coefficient of
<u>Solution:
</u>
The given expression is
As per binomial theorem, we know,
Now here a = 2x, b = (- 3y) and n = 10 and k = 0,1,2,….10
Now will be the 6 term where k =5
Now,
So, the coefficient of .
The coefficient of
1/18.
.
P = p1 x p2 = 1/6 × 2/6 = 1/18
.
Prob of getting 3 is 1/6, and prob of getting different odd number ie 1 or 5 is 2/6.
Answer:
x = -4
Step-by-step explanation:
Answer:
c)The proof writer mentally assumed the conclusion. He wrote "suppose n is an arbitrary integer", but was really thinking "suppose n is an arbitrary integer, and suppose that for this n, there exists an integer k that satisfies n < k < n+2." Under those assumptions, it follows indeed that k must be n + 1, which justifies the word "therefore": but of course assuming the conclusion destroyed the validity of the proof.
Step-by-step explanation:
when we claim something as a hypothesis we can only conclude with therefore at the end of the proof. so assuming the conclusion nulify the proof from the beginning